2008
DOI: 10.1002/bjs.6113
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing day-care open haemorrhoidectomy under local versus general anaesthesia

Abstract: Background:Day-care open haemorrhoidectomy under local anaesthesia (LH) may be the most costeffective approach to haemorrhoidectomy. This prospective randomized trial compared outcome after LH from patients' and clinical perspectives with that after day-care open haemorrhoidectomy under general anaesthesia (GH).Methods: Forty-one patients with third-degree haemorrhoids were randomized to LH (19) or GH (22). Patient demographics were comparable. A single haemorrhoid was excised in 15 patients, and two and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 60 publications
4
61
0
Order By: Relevance
“…Hemorrhoidectomy can be performed under general anesthesia; however, there may be the complications resulting from general anesthesia together with associated diseases in advanced age. Caudal or spinal anesthesia has been used as an alternative to general anesthesia for hemorrhoid surgery, but they all require a trained anesthetist and have numerous known complications [2].…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhoidectomy can be performed under general anesthesia; however, there may be the complications resulting from general anesthesia together with associated diseases in advanced age. Caudal or spinal anesthesia has been used as an alternative to general anesthesia for hemorrhoid surgery, but they all require a trained anesthetist and have numerous known complications [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, this and the previous study showed that local block did not ameliorate pain on subsequent days or enhance recovery. Nevertheless, an alternative anaesthetic method allows patients a choice26. Stapled haemorrhoidopexy under perianal local anaesthetic block is effective, convenient and acceptable to most patients compared with the same procedure under general anaesthesia, providing a similar clinical result.…”
Section: Discussionmentioning
confidence: 99%
“…Besides general, local and epidural anaesthesia, spinal anaesthesia is a common method for minor perianal procedures [2][3][4] . 'Saddle block' describes spinal anaesthesia with a low dose of hyperbaric local anaesthetics where the parts of a patient's body that would touch a saddle are anaesthetized.…”
Section: Introductionmentioning
confidence: 99%